A judicialização do acesso a medicamentos no âmbito de uma Coordenadoria Regional de Saúde do Rio Grande do Sul - Loreto, Daiane Rodrigues de (2020)
Much of the demand for lawsuits related to the right to health, against public authorities, is concentrated in the lawsuits of citizens claiming the supply of medicines. The judicialization of access to medicines has been a challenge for the management of pharmaceutical assistance within the scope of the Unified Health System (SUS) due to the weaknesses of social and economic policies in Brazil. We sought to describe the cities studied as to the deferred lawsuits for medicines in a region, characterize these lawsuits about number and origin and classify the medicines legalized by the cities in terms of their therapeutic classification and the components of Pharmaceutical Assistance (PA). This study aims actions at the local and regional level that result in the improvement of medication management and in the reduction of lawsuits against the State, in view of the financial, clinical and safety importance in the use of medication, that the judicialization represents. An ecological observational study was carried out, analyzing 7,492 lawsuits. The units of analysis were the cities that make up the Coordination, having as factor of study the deferred lawsuits of medicines sent by users and, as main outcome, the judicialized medicines grouped in the components of Pharmaceutical Assistance (PA). It was found that 73,6% (n = 5441) of legalized drugs are “off the list”, but there was an increase in the judicialization of drugs belonging to all components of PA in the period between 2014 and 2018. The classes of drugs most found in the lawsuits those used for the nervous system 26% (N = 283), cardiovascular 18% (N = 200) and for the digestive tract and metabolism 16% (N = 177). The data showed a high amount of drugs supplied through the judicial system, as well as making it possible to return to the studied cities of which drugs are being sought from the judiciary. This work is expected to contribute to the planning of more effective actions in order to reduce judicialization at the municipal and regional level.